2012
DOI: 10.17221/6469-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Adipose stem cell combined with plasma-based implant bone tissue differentiation in vitro and in a horse with a phalanx digitalis distalis fracture: a case report

Abstract: A horse suffering from an undetected hoof bone fracture was diagnosed three weeks after injury. The formation of callus tissue was detected at the fracture site. Standard orthopaedic screw application was augmented by a novel method, a combination of stem cells and plasma components. For experimental therapy, fat tissue and blood samples were collected from the patient to isolate stem cells and plasma proteins. The obtained and characterised mesenchymal stem cell population was applied to the wound area, toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…It has been proven that MSC are capable of improving metabolic control, decreasing insulin requirements, ameliorating insulin sensitivity, and increasing islets numbers in the pancreas [4, 5]. In turn, many independent clinical trials—including our own—showed that in the field of MSD treatment the MSC-based therapies have positive clinical outcomes [6]. However, the effectiveness of cellular therapies might be strongly limited by the physiological condition of engrafted cells because it affects their phenotypic plasticity (multipotency), aging, senescence, and finally oxidative stress factors accumulation that have great role in pathogenesis of both MSDs and EMS disorders.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that MSC are capable of improving metabolic control, decreasing insulin requirements, ameliorating insulin sensitivity, and increasing islets numbers in the pancreas [4, 5]. In turn, many independent clinical trials—including our own—showed that in the field of MSD treatment the MSC-based therapies have positive clinical outcomes [6]. However, the effectiveness of cellular therapies might be strongly limited by the physiological condition of engrafted cells because it affects their phenotypic plasticity (multipotency), aging, senescence, and finally oxidative stress factors accumulation that have great role in pathogenesis of both MSDs and EMS disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we attempted to treat horse bone spavin with autologous, adipose-derived mesenchymal stem cells (Ad-MSC). Such cells reside in subcutaneous adipose tissue, which is the most available and commonly used in veterinary medicine (Marycz et al 2012). We conclude that adipose stem cell injections could also be an efficient procedure for treatment of animal locomotive system disorders such as bone spavin.…”
Section: Introductionmentioning
confidence: 87%
“…One of the most promising future techniques in the medical arsenal, especially in the area of veterinary orthopedics, is regenerative medicine. There is a growing body of evidence that MSCs are useful in tissue engineering, especially in canine and equine veterinary medicine (Qui et al 2012, Marycz et al 2012a. Combinations of these cells, particularly ASCs, with specific types of NSAIDs, seem to be the most effective solution for the current orthopedic treatment of patients.…”
Section: Discussionmentioning
confidence: 99%